Active coping, resilience, post-traumatic growth, and psychiatric symptoms among early and late liver transplant survivors. Issue 3 (17th March 2023) - Lieber, Sarah R.; Baldelli, Luke; Kim, Hannah P.; Nash, Rebekah P.; Noriega Ramirez, Alvaro; Magee, Gabrielle; Barritt, Alfred S.; Evon, Donna M.; Singal, Amit G.
Abstract : Understanding survivorship experiences at different stages postliver transplantation (poat-LT) is essential to improving care. Patient-reported concepts including coping, resilience, post-traumatic growth (PTG), and anxiety/depression, have been implicated as important predictors of quality of life and health behaviors after LT. We aimed to descriptively characterize these concepts at different post-LT survivorship stages. This cross-sectional study featured self-reported surveys measuring sociodemographic, clinical characteristics, and patient-reported concepts including coping, resilience, PTG, anxiety, and depression. Survivorship periods were categorized as early (1 y or below), mid (1–5 y), late (5–10 y), and advanced (10 y or above). Univariable and multivariable logistic and linear regression modeling examined factors associated with patient-reported concepts. Among 191 adult LT survivors, the median survivorship stage was 7.7 years (interquartile range: 3.1–14.4) and median age was 63 years (range: 28–83); most were male (64.2%) and Caucasian (84.0%). High PTG was more prevalent in the early survivorship period (85.0%) than late survivorship (15.2%). High trait resilience was only reported by 33% of survivors and associated with higher income. Lower resilience was seen among patients with longer LT hospitalization stays and late survivorship stages. About 25% of survivors had clinically significant anxiety and depression, which was more frequent among early survivors and females with pre-LT mental health disorders. In multivariable analysis, factors associated with lower active coping included survivors ≥65 years, non-Caucasian race, lower levels of education, and nonviral liver disease. In a heterogeneous cohort including early and late LT survivors, there was variation in levels of PTG, resilience, anxiety, and depression at different survivorship stages. Factors associated with positive psychological traits were identified. Understanding determinants of LT survivorship has important implications for how we should monitor and support LT survivors.